(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This article is an attempt to analyze anti-proverbs related to the SARS-COV-2 pandemic, extracted from Twitter under the hashtag #covidsprichwörter. The subject of the study is all paremiological neologisms in relation to their source proverbs, in order to be able to determine which of the traditional proverbs enjoy particular popularity among Twitter users due to the number of existing variants. In order to achieve the stated goal, the topic of anti-proverbs is first analyzed. In the next part, the new formations are examined for their formal similarity with the prototypical proverbs in relation to the syntax and type of transformation.